'Hidden' innovation development through inherent and support social capitals: an experimentation in rural tourism. Issue 3 (1st September 2020) - Patluang, Kritsada
ABSTRACT: This paper focuses on 'hidden' innovation development in rural tourism propelled by combinations of social capitals. Based on questionnaire data of 147 tourism community enterprises across Thailand, findings disclose three hidden innovations – marketing, supporting process and organizational innovations – which assist the enterprises in commercializing new products and sustaining their competitiveness in new markets. The paper employs factor and hierarchical regression analyses to investigate the effects of types of social capital on the hidden innovations. The newly categorized 'inherent social capital', encompassing levels of collaboration among members and of utilization of business and information networks, breeds marketing and supporting process innovations. The 'national support social capital', embracing degrees of research network utilization and of acquaintance/participation with national development agencies/associations, spawns the three innovations. Policy implications are that social capitals are crucial for broadening the non-technological innovation landscape and that matched categories of social capital are required for augmenting specific types of innovation.